Functionalizing multifunctional Fe3O4 nanoparticle-based biocompatible, magnetic and photoluminescent nanohybrids: preparation and characterization - Nguyen, Duy Trinh; Nguyen, Phu Thuong Nhan; Tran, Thien Hien; Nguyen, Dai Hai; Vo, Dai-Viet N.; Islam, Md. Rafiqul; Lim, Kwon Taek; Vo, Sang Thanh; Bach, Long Giang (Asian J. Chem, 2019)
A combination of ring-opening polymerization (ROP) and coordination chemistry methodology has been expanded for the synthesis of a multifunctional, biocompatible, magnetic, luminescent nanohybrid complex comprising magnetite (Fe3O4) nanoparticles (MNPs), poly(ε-caprolactone) (PCL) and europium ions (Eu3+). The structural and morphological characteristic of the nanohybrid intricate were studied by appropriate spectrum and physical researches. The superparamagnetic behaviour and unique Eu3+ fluorescence properties with a high emission intensity of MNP-PCL-Eu3+ were investigated via measurements with a superconducting quantum interference equipment magnetism and fluorescence spectroscopy.